Kebolehan Pernikahan Beda Agama menurut Undang-Undang Nomor 1 Tahun 1974 dan Kompilasi Hukum Islam - Aik Fauzan Fikri; Pepe Iswanto; Ayi Ishak Sholih Muchtar (Fakultas Syari'ah | Institut Agama Islam Darussalam | IAID | Ciamis, Jawa Barat, Indonesia, 2019)
This study aims to determine the legal provisions of interfaith marriage, both according to Law Number 1 of 1974 concerning Marriage and according to the Islamic Law Compilation. The study used a content analysis method by comparing the legal provisions of interfaith marriage according to the two legal sources. The results showed that interfaith marriage according to Law Number 1 of 1974 concerning Marriage was actually prohibited, in accordance with Article 2 paragraph (1) and Article 8 letter (f) of Law No.1 of 1974. Interfaith marriage is also prohibited according to the Legal Compilation Islam according to articles 40 to 44 and article 61 that marriage is prohibited